The role of entrepreneurial literacy in mediating the influence between digital literacy and internal locus of control on SME development - Paulus Wardoyo; Endang Rusdianti; Sri Purwantini (Jurnal Manajemen dan Pemasaran Jasa, 2024)
This research aims to fill the research gap, which shows that there are challenges faced in the development of SMEs, so it is necessary to develop a model from an entrepreneurial perspective by integrating the role of entrepreneurial literacy as a mediator of digital literacy and internal locus of control. This research uses an SEM. The total sample was 125 respondent entrepreneurs in Kendal Regency. The data collection method uses a questionnaire. However, the results of this research also show that one hypothesis, namely internal locus of control, does not influence the development of SMEs. Entrepreneurial literacy is only able to mediate digital literacy in the development of SMEs, while internal locus of control does not mediate. So, the variables used in the model are pretty suitable for SME development efforts, especially those related to digital literacy and entrepreneurial literacy.